Propuesta de enfermería: embarazo en la adolescencia, aplicación del modelo de sistemas - Favela-Ocaño, María Alejandra (Universidad de Sonora, 2019)
The teenage pregnancy has become a public health problem for the risks posed not only for the adolescent but also for the product and the family, resulting in changes in the structure of society. Therefore for nurses is relevant intervention to be carried out from a viewpoint of the discipline through Betty Neuman Systems Theory , so this proposal will improve the quality through arises the structure and organization of care provided to the adolescent users.